Vivências e reflexões durante a graduação em Medicina na Universidade Federal de São Carlos - Gregório, João Paulo (Universidade Federal de São Carlos, 2021)
The Course Conclusion Paper presented to the Department of Medicine of the Federal University of São Carlos is an assessment and reflection on how the 6 years of graduation in Medicine were. The work is divided into cycles that make up the way the course was formulated. This work aims to complete the course and obtain a bachelor's degree in Medicine.
Experiences and reflections during graduation in Medicine at the Federal University of São Carlos
Keywords: Medicina UFSCar; PBL; Pandemia COVID-19; Graduação em Medicina; Medicine UFSCar; Pandemic COVID-19; Graduation in Medicine; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM